Joint resolutions relative to jurisdiction of Virginia, &c. &c. &c. (Document (Virginia. General Assembly), 1862)
1862 Joint Resolutions regarding the jurisdiction of Virginia, which resolved that its boundaries must be maintained. Of note, West Virginia, made of part of Virginia, became a state in the Union on June 20, 1863.